Las aventuras de don Chipote, o, Cuando los pericos mamen - Venegas, Daniel (Arte Público Press, 1999)
The hapless journey of the poor farmer Don Chipote de Jesús Maria Domínguez, who naively leaves behind his wife and children in Mexico to seek riches in the United States--where, he is assured, one can sweep up gold dust off the streets and "suck the nectar from the tree of life."